2012
DOI: 10.3329/jbcps.v30i1.11363
|View full text |Cite
|
Sign up to set email alerts
|

Study of EEG Findings in Patients Referred from Psychiatrists

Abstract: EEG is not so commonly used in patients attending psychiatry department. It is predominantly required to rule out any organic cause behind the behavioral changes. Purpose of this study was to assess the referred cases from psychiatry department and determine the clinical factors associated with an abnormal EEG in patients with psychiatric problem. We retrospectively reviewed and analyzed the data of all the cases referred to EEG lab. Introduction:Electroencephalography (EEG) is the recording of electrical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…However, spike and wave where reported in Chowdhary et alas common EEG pattern. 8 The majority had EEG abnormality in our study and that of Shrestha et al 7 However, Bhagat et al reported normal EEG in the majority which was done among the epileptics. 9 This difference is expected as EEG is a cross sectional record of the brain activity and 50% of patients with epilepsy can have normal EEG, and therefore, does not exclude epilepsy.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, spike and wave where reported in Chowdhary et alas common EEG pattern. 8 The majority had EEG abnormality in our study and that of Shrestha et al 7 However, Bhagat et al reported normal EEG in the majority which was done among the epileptics. 9 This difference is expected as EEG is a cross sectional record of the brain activity and 50% of patients with epilepsy can have normal EEG, and therefore, does not exclude epilepsy.…”
Section: Discussionsupporting
confidence: 53%
“…5 , 6 Similar finding was reported in various studies. [7][8][9][10] Studies suggest male at higher risk for seizure and epilepsy. 5 This explains the higher proportion of male in our study for EEG evaluation which was supported by different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 EEG referral from psychiatrists reported abnormality in 40 % of the study population in Bangladesh, 46.47% in our study, 17.6% in the study by O'Sullivan, 11.3% in the study by Lam but only 8.2% in the African study. [14][15][16][17] This disparity could be due to variation in sample size, sample type as well as interpreter variability. Different studies showed few or no positive finding in EEG in psychiatric conditions, including ours.…”
Section: Resultsmentioning
confidence: 99%
“…15 However, spike and wave were reported in Chowdhary et al as common EEG pattern. 14 In a series of 2648 patients with the unquestionable diagnosis of the seizure by Kershman et al, 46.5% had focal changes while 15.0% had a diffuse generalized abnormality in their scalp recordings of EEG. 30 In our study, EEG was done in 245 patients in which EEG was normal in 64.1% patients and abnormal in 35.9% patients, of which 19.2% had hemisphere and 10.6% had a generalized epileptic discharge.…”
mentioning
confidence: 97%